Qualitative and Quantitative Methods in Libraries Journal Special Issue: Social Justice, Social Inclusion - Mehra, Bharat (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
The theme of this QQML Journal Special Issue “Social Justice, Social Inclusion” is in response to an urgent need to showcase social justice concerns in library and information science (LIS), a discipline that has long servicerooted traditions, yet, seldom are library services, user-centered practices, and information products articulated in terms of social justice constructs, vocabularies, and results (Mehra, Rioux, and Albright, 2010; Mehra, Albright, and Rioux, 2006). This Special Issue includes papers that describe and analyze LIS experiences in terms of action-oriented and socially relevant outcomes achieved via information-related work. Authors present their experiences in LIS work, practice, education, service design, and program implementation in ways that further community-wide progressive changes partnering with, and, on behalf of people on society’s margins. They engaged in research and teaching while keeping their focus on social impact and community involvement.